A Comparative Analysis of the Utilization of Learning Media Applications in Supporting Teaching and Learning Activities of Lecturers and Cadets After the Covid-19 Pandemic at the Jakarta College of Shipping Sciences and the Bali Land Transportation Polytechnic - Wibowo, Titis Ari; Jarot Delta Susanto; Hidayah, Ferro (Meteor STIP Marunda, 2023)
STIP Jakarta is an educational institution under the Ministry of Transportation that has used a Learning Management System (LMS) in the form of an online learning application, namely Ed-link, during the Covid-19 pandemic and is still used today, with the aim of increasing access to learning for lecturers and cadets in the process. Teaching and learning activities at STIP Jakarta, apart from following the government's advice on implementing Social Distancing during the pandemic, however, there are still many obstacles faced in the implementation process. Similar use is also carried out at the Bali Land Transportation Polytechnic (Poltrada) which also has a similar Learning Management System (LMS), namely the use of the Smart Campus application to support learning media during the Covid 19 pandemic and the application is still used today for lecturers and cadets. The purpose of this research is to determine a comparative analysis of the two educational institutions, namely STIP and Poltrada Bali, regarding the influence of the use of the Ed-link and Smart Campus learning media applications in supporting the process of teaching and learning activities for lecturers and cadets involved in them. The research method used was quantitative descriptive by creating a questionnaire instrument which was distributed to 131 STIP lecturer and cadet respondents and 140 Bali Police lecturer and cadet respondents. Data analysis processing uses the IBM SPSS version 27.0.1 application and interpretation of the results is used as evaluation material and input to STIP institutions.